Design of Optical Collimator System for Vehicle Speed Gun using Non-Imaging Optics - Le Minh Nhut; Thanh Tuan Pham; Tien Dung Tran; Vu Dinh Huan; Seoyong Shin (International Journal of Renewable Energy Development, 2023)
Vehicle speed guns are usually used in normal sunlight conditions (daytime). If we want to use vehicle speed guns in low light conditions (nighttime), the illuminator is needed to provide sufficient light for the vehicle speed gun to take photos. The illuminator must fulfill two requirements: (i) using the infrared wavelength to ensure that the driver is not startled by dazzling eyes by the illuminator of the proposed speed gun system and (ii) high energy efficiency to make the illuminator compact leading to the use a small battery system to improve the portable of the proposed vehicle speed gun. In this study, an illuminator using a collimator system designed by using non-imaging optics is introduced. LEDs with infrared wavelength are chosen from the library of LightToolsTM, the structure of collimated is designed to transfer the illumination from the LEDs array to a square area of 3x3 m2 to cover the vehicle to detect the vehicle number plate. The design process is built based on the conservation of optical path length in the Matlab program. After that, the designed collimator is simulated in LightToolsTM software. The promising results of the simulation in LightToolsTM show that the collimator can efficiently transfer light from the LED array to the target area with a uniformity of about 70 % and optical efficiency of about 80 %.